(3GdcGaj aj Yde GdbhGais - (3CHh GdMSf Ydj Hf eMeO Hf MSf GdQHGWi GdeYQha HGHf HQis ((3YHO GdhGMO Hf CMeO Hf eMeO GdMSfi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg ceG jfHZi dceGdg aCbhd Ef Yde GdbhGai Chdi eG Yfi Hg ef jfJei Edi GdYdhe GdCOHjI hbO bUOJ HhVYi gPG GdeNJUQ GdedbH HGdcGai ai Yde GdbhGai LYdJ efWhjkG Ydi ebOeI haUdjf hKdGKI CbSGe s
(3BNQgG (B:s
(3jfJgi HHGH GdZdh hgh JMQjQ GdQhi GdeajO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg hQbI ef cJGH TQM YQhV GHf GdSbGWs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs